Forced wetting of stainless steel by distilled water drop - Ponomarev K. O. Konstantin Olegovich; Popov Yu. S. Yury Sergeevich; Orlova E. G. Evgeniya Georgievna; Kirichenko D. P. Dmitry Pavlovich (2017, 2017)
Title screen